Activation of olefin metathesis complexes containing unsymmetrical unsaturated N-heterocyclic carbenes by copper and gold transmetalation. Issue 77 (9th September 2019) - Kamal, Fadwa; Colombel-Rouen, Sophie; Dumas, Adrien; Guégan, Jean-Paul; Roisnel, Thierry; Dorcet, Vincent; Baslé, Olivier; Rouen, Mathieu; Mauduit, Marc
Abstract : The activation of latent ruthenium complexes containing two unsymmetrical NHCs by copper and gold transmetalation leads to impressive initiation rates in olefin metathesis. Abstract : The activation of ruthenium-indenylidene complexes containing two unsymmetrical unsaturated N-heterocyclic carbenes (u2-NHCs) by a transmetalation process is reported. The use of copper(i ) or gold(i ) chlorides promotes the rapid trapping of one NHC ligand, which releases the catalytically active Ru-species. Impressive initiation rates with full-conversions are observed within one minute. This practical protocol demonstrates excellent catalytic performances in various ring-closing metathesis (RCM) and self-metathesis (SM) reactions.